Navigating realities: a pornography literacy and sexual health curriculum for high school students - Balliet, Margot E.; Ford, Jessie V. (Frontiers in Education, 2025)
The rising prevalence of internet pornography consumption among adolescents has created a need for proactive approaches to pornography literacy within sex education. This article aims to both introduce the “Navigating Realities” curriculum and advocate for an expanded approach to pornography literacy education that integrates comprehensive media literacy, critical analysis, and a sex-positive framework. This evidence-informed curriculum was developed based on a literature review on adolescent pornography consumption, its impact on sexual attitudes and behaviors, and documented gaps in existing sex education programs. Methodologically, the curriculum is grounded in backward design, the cultivation theory of mass media, and the triangle of sexual health, rights, and pleasure. Guided by these frameworks, Navigating Realities pursues three overarching aims: (1) promote critical thinking and media literacy, (2) foster healthy relationships, and (3) encourage responsible digital behavior. These aims guide the pedagogical approach, which incorporates a combination of knowledge-based activities, social norms exploration, and skill-building exercises. The curriculum emphasizes the distinction between fantasy and reality in sexual content, body image, consent, and the portrayal of violence, while reinforcing healthy relationship skills and safe digital practices. As a result, “Navigating Realities” serves as a proposed evidence-informed educational framework, tailored to high school students aged 15–18, that supports them in critiquing explicit content. Future applications will include pilot testing and broader implementation, underscoring the need for ongoing research and funding to ensure the effectiveness of comprehensive sex education initiatives.